Multiple autocrine growth factors modulate vascular smooth muscle cell growth response to angiotensin II. - Itoh, H (1993)
Angiotensin (Ang) II stimulates hypertrophic growth of vascular smooth muscle cells (VSMC). Accompanying this growth is the induction of the expression of growth-related protooncogenes (c-fos, c-jun, and c-myc), as well as the synthesis of the autocrine growth factors, such as PDGF-A and TGF-beta 1. In this study, we demonstrate further that Ang II also induces the synthesis of basic fibroblast growth factor (bFGF), a potent mitogen for VSMC. To examine how these factors interact to modulate the growth response of VSMC to Ang II, we used antisense oligomers to determine the relative contribution of these three factors. Treatment of confluent, quiescent smooth muscle cells with specific antisense oligomers complementary to bFGF, PDGF-A, and TGF-beta 1 efficiently inhibited the syntheses of these factors. Our results demonstrate that in these VSMC, TGF-beta 1 affects a key antiproliferative action, modulating the mitogenic properties of bFGF. Autocrine PDGF exerts only a minimal effect on DNA synthesis. An imbalance in these signals activated by Ang II may result in abnormal VSMC growth leading to the development of vascular disease.